Vineyard thermal stress assessment through the combination of in-situ and remote sensing technology - Felício, T.; Postolache, O. A.; Rodrigues, M. J.; Sebastião, P. (2023 IEEE Sensors Applications Symposium (SAS), 2023)
Precision viticulture is crucial for optimizing vineyard productivity and sustainability, particularly as climate change poses increasing threats to plant health. This work explores the development of an Internet of Things (IoT) system for the evaluation and mitigation of thermal stress in vineyards, an\ abiotic stress factor that can adversely affect growth and productivity. The proposed system combines in-situ sensing and remote sensing technologies, which also include the use of thermography imagery, to collect real-time data on parameters such as air relative humidity, soil moisture, air/leaf/soil temperature, and luminosity. Through the integration of different sensing channels, the study establishes correlations between the monitored parameters, enabling a more comprehensive assessment of vineyard health status with respect to thermal stress.